Join IDNLearn.com and start exploring the answers to your most pressing questions. Ask your questions and receive detailed and reliable answers from our experienced and knowledgeable community members.
Sagot :
Sure, let's solve the given expression step-by-step.
We need to find the value of [tex]\((a - b - c)^2 - (a - b + c)^2\)[/tex].
### Step 1: Expand Each Square
First, let's expand each term separately.
For [tex]\((a - b - c)^2\)[/tex]:
[tex]\[ (a - b - c)^2 = (a - b - c)(a - b - c) \][/tex]
Using the distributive property (also known as the FOIL method):
[tex]\[ = (a - b - c)(a - b - c) = a(a - b - c) - b(a - b - c) - c(a - b - c) = a^2 - ab - ac - ab + b^2 + bc - ac + bc + c^2 \][/tex]
Combine like terms:
[tex]\[ (a - b - c)^2 = a^2 - 2ab + b^2 - 2ac + 2bc + c^2 \][/tex]
For [tex]\((a - b + c)^2\)[/tex]:
[tex]\[ (a - b + c)^2 = (a - b + c)(a - b + c) \][/tex]
Again, using the distributive property:
[tex]\[ = (a - b + c)(a - b + c) = a(a - b + c) - b(a - b + c) + c(a - b + c) = a^2 - ab + ac - ab + b^2 - bc + ac - bc + c^2 \][/tex]
Combine like terms:
[tex]\[ (a - b + c)^2 = a^2 - 2ab + b^2 + 2ac - 2bc + c^2 \][/tex]
### Step 2: Subtract the Two Expanded Expressions
We need to find the difference between these two expanded forms:
[tex]\[ (a - b - c)^2 - (a - b + c)^2 \][/tex]
Using the expanded results:
[tex]\[ = \left(a^2 - 2ab + b^2 - 2ac + 2bc + c^2\right) - \left(a^2 - 2ab + b^2 + 2ac - 2bc + c^2\right) \][/tex]
Distribute the subtraction:
[tex]\[ = a^2 - 2ab + b^2 - 2ac + 2bc + c^2 - a^2 + 2ab - b^2 - 2ac + 2bc - c^2 \][/tex]
### Step 3: Simplify the Expression
Combine like terms by simplifying:
[tex]\[ = a^2 - a^2 - 2ab + 2ab + b^2 - b^2 - 2ac - 2ac + 2bc + 2bc + c^2 - c^2 = 0 - 4ac + 4bc \][/tex]
So, the simplified form of the expression is:
[tex]\[ 4c(-a + b) \][/tex]
Thus,
[tex]\[ (a - b - c)^2 - (a - b + c)^2 = 4c(-a + b) \][/tex]
This is the final result.
We need to find the value of [tex]\((a - b - c)^2 - (a - b + c)^2\)[/tex].
### Step 1: Expand Each Square
First, let's expand each term separately.
For [tex]\((a - b - c)^2\)[/tex]:
[tex]\[ (a - b - c)^2 = (a - b - c)(a - b - c) \][/tex]
Using the distributive property (also known as the FOIL method):
[tex]\[ = (a - b - c)(a - b - c) = a(a - b - c) - b(a - b - c) - c(a - b - c) = a^2 - ab - ac - ab + b^2 + bc - ac + bc + c^2 \][/tex]
Combine like terms:
[tex]\[ (a - b - c)^2 = a^2 - 2ab + b^2 - 2ac + 2bc + c^2 \][/tex]
For [tex]\((a - b + c)^2\)[/tex]:
[tex]\[ (a - b + c)^2 = (a - b + c)(a - b + c) \][/tex]
Again, using the distributive property:
[tex]\[ = (a - b + c)(a - b + c) = a(a - b + c) - b(a - b + c) + c(a - b + c) = a^2 - ab + ac - ab + b^2 - bc + ac - bc + c^2 \][/tex]
Combine like terms:
[tex]\[ (a - b + c)^2 = a^2 - 2ab + b^2 + 2ac - 2bc + c^2 \][/tex]
### Step 2: Subtract the Two Expanded Expressions
We need to find the difference between these two expanded forms:
[tex]\[ (a - b - c)^2 - (a - b + c)^2 \][/tex]
Using the expanded results:
[tex]\[ = \left(a^2 - 2ab + b^2 - 2ac + 2bc + c^2\right) - \left(a^2 - 2ab + b^2 + 2ac - 2bc + c^2\right) \][/tex]
Distribute the subtraction:
[tex]\[ = a^2 - 2ab + b^2 - 2ac + 2bc + c^2 - a^2 + 2ab - b^2 - 2ac + 2bc - c^2 \][/tex]
### Step 3: Simplify the Expression
Combine like terms by simplifying:
[tex]\[ = a^2 - a^2 - 2ab + 2ab + b^2 - b^2 - 2ac - 2ac + 2bc + 2bc + c^2 - c^2 = 0 - 4ac + 4bc \][/tex]
So, the simplified form of the expression is:
[tex]\[ 4c(-a + b) \][/tex]
Thus,
[tex]\[ (a - b - c)^2 - (a - b + c)^2 = 4c(-a + b) \][/tex]
This is the final result.
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Thank you for choosing IDNLearn.com. We’re committed to providing accurate answers, so visit us again soon.